FORMULATION AND CONCLUSION OF INTERNATIONAL TREATIES IN EUROPEAN UNION AND «SPECIAL ROLE» OF GREAT BRITAIN VIS-À-VIS TO UNION - Assem, Жумабекова (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2015)
The purpose of this article is a complex analysis of the main treaties of European Union which regulate legal aspects of concluding international treaties in the framework of member states, as well as outside the union with third countries. Also in the article considers «especial role» of Great Britain which represents interesting in our view in the system of «variable geometry».